Acute hepatic steatosis: a helpful diagnostic feature in metallic phosphide–poisoned horses. (March 2018) - Fox, Jonathan H.; Porter, Brian F.; Easterwood, Leslie; Hildenbrand, Justin R. V.; Hélie, Pierre; Smylie, James; O'Toole, Donal
Metal phosphides, particularly zinc and aluminum phosphide, occasionally poison horses and other equids following their use as rodenticides and insecticides. Grain-based aluminum phosphide baits are used to control rodents such as prairie dogs. The clinical course in intoxicated horses is short (<24–48 h), and animals may be found dead. Hepatic lesions caused by phosphine poisoning are not well described. Laboratory confirmation depends on detecting phosphine gas in gastric contents. Eight horses and a mule were exposed to zinc phosphide used to control prairie dogs on a Wyoming ranch. Three of 9 exposed equids developed some combination of sweating, ataxia, anxiety, and colic; 2 died acutely, and 1 recovered. A diagnosis of zinc phosphide was made by detecting phosphine in stomach contents from a horse and a mule. The liver was pale and swollen in the affected horse, which died after a clinical course of ~12 h. Other changes were generalized congestion and edema, pulmonary edema, and acute cerebrocortical edema. There was diffuse hepatocellular microvesicular steatosis. Similar histologic lesions were present in 7 equine livers from 2 previously published episodes of metallic phosphide poisoning. Older lesions (>24 h of clinical signs) had centrilobular hepatic necrosis with congestion and a mixture of microvesicular and macrovesicular steatosis. Phosphine poisoning should be considered in horses that die acutely and are found to have steatosis, either with or without hepatocellular necrosis.